Description of Self-Stigma Among Children in Conflict with the Law - Nur Oktavia Hidayati; Evita Peron; Desy Indra Yani (Universitas Muhammadiyah Semarang, 2022)
The community's stigma of perpetrators of crime, leading prisoners to have a self-sigma that is believed to be his identity, including children in conflict with the law at Lembaga Pembinaan Khusus Anak (LPKA). Self-stigma makes a person feel worthless, dangerous, and having difficulty reintegrating into society. The purpose of this study was to find a description of self-stigma of children in conflict with the law in LPKA. This type of research was quantitative descriptive, with a population of 113 children in conflict with the lawren, using consecutive sampling techniques to 88 people. The instrument used was Self-Stigma of Individuals with Criminal Records (SSICR), with validity values between 0.320-0.914 and realibility values for perceived stigma 0.86, stereotype agreement 0.71, and internalized stigma 0.85. Data was analyzed by univariat analysis. The result showed that median value of internalized stigma which was the last process of self-stigma was lower than the two previous domains, so the level of self-stigma of children in conflict with the law at LPKA was said to be low. Based on the results, self-stigma of children in conflict with the law at LPKA were low, it needs attention from the LPKA to improve education development, so that children in conflict with the law form a self-stigma, that they have good intelligence.